Analisis Kebutuhan Pengunaan Game Edukatif Wordwall terhadap Hasil Belajar Kelas III SD pada Materi Akibat Tidak Mematuhi Aturan - Titah Afit Wahyuni; Fera Dwidarti; Wendri Wiratsiwi (Paedagogie, 2026)
The purpose of this research is to investigate the viability, usability, and efficacy of using Wordwall as a foundation for an interactive learning media unit covering the subject of “Akibat Tidak Mematuhi Aturan” with students in third grade of primary school. Analyzing, designing, developing, implementing, and evaluating are the steps that make up the ADDIE development paradigm, which was used in this study as an R&D approach. Seventeen third graders from SDN Pondokrejo participated in the research. Methods such as exams, interviews, and observation were used to gather data. Pre- and post-test questions, together with expert validation sheets, questionnaires for both teachers and students, and other relevant tools were utilized. Evaluations conducted by material experts, language experts, and media experts confirmed that the Wordwall-based learning media that were created fulfilled the validity requirements. The medium was deemed practical by both instructors and students, and it was shown to effectively improve students' learning outcomes, as seen by the rise in posttest scores. Consequently, wordwalls are a great fit for primary schools looking for a fresh, dynamic, and interesting way to teach their students.